1987
DOI: 10.1007/bf02370385
|View full text |Cite
|
Sign up to set email alerts
|

Water stress effects on leaf elongation, leaf water potential, transpiration, and nutrient uptake of rice, maize, and soybean

Abstract: A pot experiment was conducted in the greenhouse to determine and compare the responses of rice (Oryza sativa L. var. IR36), maize (Zea mays L. var. DMR-2), and soybean (Glycine max [L.] Merr. var. Clark 63) to soil water stress. Leaf elongation, dawn leaf water potential, transpiration rate, and nutrient uptake in stressed rice declined earlier than in maize and soybean. Maize and soybean, compared with rice, maintained high dawn leaf water potential for a longer period of water stress before leaf elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 19 publications
4
84
0
12
Order By: Relevance
“…Plants that evolved under drought conditions were associated with reduced C : N ratios (figure 2) and thus may have experienced a relatively higher nitrogen environment. Because plants have a more difficult time accessing nitrogen resources in dry environments [38,39], such an evolutionary effect that increases nitrogen availability could facilitate plant growth in dry soils and lead to positive eco-evo feedbacks between plants and soil microbes. Alternatively, plants that evolved under drought conditions may produce less litter or delay senescence relative to plants that evolved in wet conditions and provision the soil with less carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Plants that evolved under drought conditions were associated with reduced C : N ratios (figure 2) and thus may have experienced a relatively higher nitrogen environment. Because plants have a more difficult time accessing nitrogen resources in dry environments [38,39], such an evolutionary effect that increases nitrogen availability could facilitate plant growth in dry soils and lead to positive eco-evo feedbacks between plants and soil microbes. Alternatively, plants that evolved under drought conditions may produce less litter or delay senescence relative to plants that evolved in wet conditions and provision the soil with less carbon.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, drought conditions may reduce soil-N mineralisation, thus lowering the N availability. Besides, a reduced N uptake in the crop may also be attributed to a decreased transpiration rate, to transport N from roots to shoots (Tanguilig et al 1987). Thus, it is well established that drought reduces both nutrient uptake by the roots and transport them from the roots to the shoots, because of restricted transpiration rates and impaired active transport and membrane permeability (Alam 1999) probably a result to the leaf area restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Prasertsak and Fukai (1997) showed that the reduction in dry matter production under water defi cits in an upland fi eld was associated with a reduction in the amount of N uptake. O' Toole and Baldia (1982) and Tanguiling et al (1987) suggested that the transpiration of rice plants declined under water-defi cit conditions, which reduced the amount of N uptake. Changes in surface soil moisture conditions from near saturation to water defi cits may also reduce N availability (i.e., the amount of mineralized N in the rhizosphere soil) (Kumar and Goh, 2000), as is frequently observed in rainfed lowland rice (Wade et al, 1998).…”
Section: Dry Matter Productionmentioning
confidence: 99%